An Overview of Species Concept used in Spiders Taxonomy with an Emphasis on Mating Structures - Omid Mirshamsi; Sepideh Shafaie; Mansour Aliabadian; Majid Moradmand; Yuri Marusik (تاکسونومی و بیوسیستماتیک, 2017)
Although arachnology has a long-standing history but the main progress in spiders taxonomy is related to the Golden Age of Araneology. Indeed, from this period onward the copulatory organs (primary and secondary structures) found their true positions in new species description and delimitation. But it is surprising that only a few arachnologists have taken a clear stand about species, considering the inordinate number of concepts. According to the importance of species in taxonomy, the aim of this paper is to present an acceptable definition of the species concept and to investigate the role of copulatory structures in species identification. Studies have shown that species are reproductive communities that are genetically isolated from such other communities. Proceeding relatively independently evolution in different species implies that the species concept is not a universal and comprehensive concept for all the species. On the other hand, as the genital traits often evolve faster than other morphological characters, the role of genital traits is undeniable in distinguishing closely related species and species delimitation. Anyway, there is no certainty about the species-specificity of the copulatory structures. As a final result, it should be noted that variation studies and morphological-molecular congruence analyses will probably advance our knowledge to understand the significance of copulatory structures in the systematics of different spider species.